2019
DOI: 10.15678/eber.2019.070311
|View full text |Cite
|
Sign up to set email alerts
|

Digital Marketing Communication from the Perspective of Individual Consumers: A Cross-Country Comparison

Abstract: A B S T R A C T Objective:The main objective of this article is to identify social media (SM) usage in communication between individual consumers and producers in different countries. The considerations in the article are focused on consumers' perspective. Research Design & Methods:The article takes a deductive approach and the aim is to answer two research questions: For what purpose do consumers communicate with companies via SM? Does the frequency of using the most popular SM in the researched countries inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…In the following table we present the results of the Spearman correlation. In her study, Bartosik-Purgat (2019), utilizing the Spearman Correlation, analysed the digital marketing or social media usage by consumers in their communications with companies in certain countries of Europe, Asia and the United States. Her results showed few differences among these countries in relation to the use of social media for interpersonal and marketing communication purposes.…”
Section: Resultsmentioning
confidence: 99%
“…In the following table we present the results of the Spearman correlation. In her study, Bartosik-Purgat (2019), utilizing the Spearman Correlation, analysed the digital marketing or social media usage by consumers in their communications with companies in certain countries of Europe, Asia and the United States. Her results showed few differences among these countries in relation to the use of social media for interpersonal and marketing communication purposes.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of all these, current changes in the global entrepreneurial ecosystem as a result of rapid technological changes have had a greater impact on the larger SMEs' activities, affecting rural micro-enterprises the most [9,10]. Moreover, a combination of financial constraints and low skills further exacerbate the impacts of rapid technological changes for micro-SMEs as the fierce competition is now fueled by a new digital business environment in which technology plays an increasingly important role in every single business activity [11]. Nonetheless, SMEs of all sizes need to ride the new technological wave in order to remain relevant in the market.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, SMEs of all sizes need to ride the new technological wave in order to remain relevant in the market. Explaining the importance of the role of technology to SMEs, the results of a study conducted by [11] on four countries, namely Poland, the USA, Turkey, and China, found that social media was the main medium of communication between customers and companies, SMEs in this context. Never before has the role of technology in business proven to be so compelling than in the recent context when most retail economic activities were 'taken over' by technology, in particular, during the COVID-19 pandemic where human movements were severely restricted [12].…”
Section: Introductionmentioning
confidence: 99%
“…Digital media enables interconnectivity and real time data coupled with the possibility of machine learning, and automation that is able to be applied to digital marketing [4] [5]. Therefore, communication related to marketing subject has entered the industry 4.0 [6] [7]. When the marketing and communication has entered the industry 4.0, so does the entrepreneurship [8].…”
Section: Introductionmentioning
confidence: 99%